Empowering Migrant Youth through Participatory Approach in Social Work - Bertozzi, Rita (Participatory Social Work: Research, Practice, Education, 2019)
Young immigrants have the greatest risk of exclusion in many European countries, due to educational inequalities, both in outcomes and opportunities, and to socio-economic family conditions. The paper proposes a reflection on two projects involving immigrant minors in Italy. The first is a participatory research project on child labour/work conducted with a group of working immigrant teenagers; the second is a tutoring project conducted with immigrant university students to support foreign students at risk of failure. Through participatory approaches, the two experiences read differently the child work and the school failure of the children of immigrants, highlighting the different perspectives with which the two issues can be analyzed and addressed. It shows the potential of participatory methods in offering different perspectives and in empowering young people, as well as the possible implications for social work. The results provide useful insights for working with immigrant subjects in other areas as well.